2015
DOI: 10.1177/0003122414564998
|View full text |Cite
|
Sign up to set email alerts
|

Contact Theory in a Small-Town Settler-Colonial Context

Abstract: This article builds on group position theory and the subcategorization model of intergroup contact by illustrating how, in a small-town settler-colonial context, contact tends to reproduce, rather than challenge, the inequitable racial structure. In Northwestern Ontario, Indigenous-settler relations are characterized by widespread intergroup marriage and friendship as well as pervasive prejudice and discrimination. Using 18 months of fieldwork and 160 interviews and surveys with First Nations, Métis, and non-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(17 citation statements)
references
References 52 publications
(116 reference statements)
1
16
0
Order By: Relevance
“…In view of the above, studies testing the contact hypothesis should consider the frequency and valence of the intergroup contact. Although many studies indicate that direct intergroup contact reduces prejudice, others suggest that the effect of contact is selective (Denis, 2015;Jackman & Crane, 1986).…”
Section: H5: the Effect Of The Valence Of Intergroup Contact Outweighs That Of The Frequency Of Intergroup Contactmentioning
confidence: 99%
“…In view of the above, studies testing the contact hypothesis should consider the frequency and valence of the intergroup contact. Although many studies indicate that direct intergroup contact reduces prejudice, others suggest that the effect of contact is selective (Denis, 2015;Jackman & Crane, 1986).…”
Section: H5: the Effect Of The Valence Of Intergroup Contact Outweighs That Of The Frequency Of Intergroup Contactmentioning
confidence: 99%
“…It has been suggested that Indigenous peoples continue to be the most disadvantaged group in Canada, with instances of racism described as being ‘alarmingly high’ (Morrison et al, 2014; Statistics Canada, 2015). Indigenous communities and resources continue to be overseen by federal legislation (The Indian Act), and efforts to achieve equality and compensation for historical injustices, and their active exercise of treaty rights, are opposed by many non-Indigenous Canadians (Denis, 2015). In addition, they suffer disproportionate rates of physical illnesses (diabetes, HIV/AIDS, hepatitis, severe respiratory illnesses) and mental health disturbances (depression, posttraumatic stress, drug and alcohol addiction, suicide) (Kirmayer, 2014).…”
Section: Studymentioning
confidence: 99%
“…7 It is worth noting that the logical presentation of the categories normalizes white Canadian as the "norm" from which all others deviate. 8 Given the current and historical context of Indigenous-Canada relations (e.g., see Taiaiake, 1999;Ramos, 2006;Denis, 2015) the qualification should be made that the reported rates might have been higher for Indigenous people had a specific question been asked about discrimination related to being Indigenous. Further is that any such question might get at overt discrimination but not colonization.…”
Section: Resultsmentioning
confidence: 99%